Środowiskowe opracowania kartograficzne PIG - możliwości wykorzystania w zagospodarowaniu dorzecza Odry = The environment mapping publications of Polish Geological Institute - as applied in the environment at management in the Odra river basin - Sikorska-Maykowska, Małgorzata; Strzelecki, Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Continuous edition of the maps at the scale 1 : 50 000, using GIS system, compiled at Polish Geological Institute are presented in the paper. This inclucles: Geoenvironmental Map of Poland, Hydrogeological Map of Poland and Geological Map of Poland. Information stored in the map database allows their application in management plans of Odra River Basin.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)